Genetic Polymorphisms of Cytotoxic T-Lymphocyte Antigen 4 in Primary Biliary Cholangitis: A Meta-Analysis - Xing-Chen Yang; Masayuki Fujino; Song-Jie Cai; Shao-Wei Li; Chi Liu; Xiao-Kang Li (Journal of Immunology Research)
Background and Aim. The connection between gene polymorphisms of cytotoxic T-lymphocyte-associated protein 4 (CTLA4) and primary biliary cholangitis (PBC) is still vague and blurred. The purpose of this study is to precisely estimate the association of the polymorphisms of CTLA4 with the risk of PBC by using a meta-analysis. Methods. PubMed and the Chinese National Knowledge Infrastructure (CNKI) database were used to search correlative literatures, and the documents which were about the relationships between the polymorphisms of CTLA4 (rs231775, rs231725, rs3087243, and rs5742909) and PBC were collected as of June 2016. The strength of correlation based on odds ratios (ORs) and its 95% confidence intervals (95%CIs) was computed by STATA. Results. Generally, in rs231775, a significant risk was found in G allele, the value of OR was 1.32, and its 95%CI was 1.19 to 1.47. The same situation was found in A allele of rs231725, the value of OR was 1.33, and its 95%CI was 1.22 to 1.45. As genotypic level, different genotypic models were also found to have obvious relevance with PBC in rs231775 and rs231725. No obvious connections were found in other SNPs. Conclusion. This study indicated that the polymorphisms of rs231775 and rs231725 would be the risk factors of PBC.